EDİP CANSEVER'İN HAYATI, ESERLERİ, ŞİİRLERİNİN YAPI VE TEMA BAKIMINDAN İNCELENMESİ - YATKIN, NAZAN (Fırat Üniveristesi, 2000)
Edip Cansever was born on the 8 th of August 1928 in Istanbul. He entered a new period with each of his work. He is one of the founder of thç "Secondory New" poem movement, According to this movement his poems can be classified in to three periods. This classification will show us his poetry style. These periods are classified with his three books; before "secondary new", "around midafternoon" and "peace and harmony". Before secondory new can be classified as his Inexperience perrod. His mastery storted with "Secondory New", His works can be choracterized as well- settled, mature and conteporary. Edip Cansever match with every movement and he opened the door of Innovation, He is not the poet of monotonous poems. He recognized the writers and poets of western world and tried to synthesize with our conven tionol literature. After secondary new his poetry reached to peak. Edip Cansever was an existen tialist and basic element of his poem was "death and loneliness: Vision of external world was used as readiness to main concept, Conflicts and contradictions were used to exhibit the tragedy of humon being. His starting point was his egos and way of life. U.Nazan YATKIN
Examining the Edip Cansever's life, works and poems from the viewpoint of structure and accent
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Biyografi; Biography; Türk Dili ve Edebiyatı; Turkish Language and Literature